Structural, Mechanical, FTIR, SHG and Thermal Studies of L-HTFA Single Crystals Grown by Solution Method - P. Selvarajan2*, S.L. Rayar1, (Recent Research in Science and Technology, 2010)
Single crystals of L-histidine trifluroacetate(L-HTFA) have been grown successfully by solution growth method from its aqueous solution. Single crystals of L-HTFA having dimensions 20 x 5 x 3 mm3 have been grown by slow evaporation method at room temperature in a growth period of 3 weeks. The grown crystals have been subjected to X-ray diffraction(XRD) studies to identify the morphology and structure. The Differential Scanning Calorimetry(DSC) and TG/ DTA studies confirm the thermal stability of the grown crystal. The FTIR study reveals bonding interaction of trifluroacetate and histidine in the crystal lattice. The NLO property of the crystals has been confirmed by Kurtz powder test. Mechanical property of the grown crystal was carried out by measuring microhardness number.